Influência da internet no processo de decisão de compra de produtos eletroeletrônicos do consumidor de baixa renda na Grande Fortaleza - Hollanda, Alexandre Pinho Pessoa de (2014)
The main purpose of the present study is to analyze the internet influence in the decision-making process on purchasing electronic goods by low-income consumers in the city of Fortaleza. The specific objectives intended to bring up the low-income consumer´s profile in the purchase decision making process; investigate which profile would be most influenced by the internet in each phase and to identify in which internet phase(s) influence the most this consumer. The theme choice was motivated by the growth of the low-income market importance throughout recent years on the Brazilian economy and by the growing influence that internet does on the purchasing process on such consumers, mainly related to the electronic product acquisition. The theoretical references were organized over the major concepts on consumer behavior, purchase decision models, focused on the model of Blackwell et al (2011) which was used as the base of this study, being simplified and adapted to the internet reality, the Brazilian low-income market and its relationship with the internet and the electronic purchases. Regarding the study methodology, it can be classified as exploratory and descriptive with quantitative nature through the use of the survey research method by applying a questionnaire in a non-probabilistic sample accidental, comprised by 517 respondents. The data analysis was done through statistical multivariate analyzis techniques such as exploratory and confirmatory factor analysis, hypothesis test and tree regression modeling with the use of SPSS and Amos softwares. The found results allowed us to confirm the hypothesis that low-income young people are more influenced by the internet on their purchase process. That the higher the internet usage frequency, the greater is its influence on the purchasing decision process and that the information search phase combined with the alternative evaluation phase, are the ones most influenced by the internet on the purchase process. The information obtained in this study may be useful for organizations, field researchers and other interested parties on low-income markets. Finally, the study had its limitation regarding the size and type of the adopted sampling and as its geographical region. The study may be amplified, in order to comprehend the consumer behavior in other Brazilian capitals or from other variables.